Differences in surface roughness of enamel after whey-extract application and CPP-ACP in post extracoronal-tooth bleaching - Afiatul Mukarromah; Irfan Dwiandhono; Dian Noviyanti Agus Imam (Majalah Kedokteran Gigi Indonesia, 2018)
Demineralization is a process of partial or full tooth mineral loss which caused by acidic environment, for example the side effect of extracoronal bleaching treatment. Demineralization increases enamel surface roughness which leads plaque accumulation. Whey extract and calcium phosphopeptide-amorphous calcium phophate (CPP-ACP) contain calcium and phosphate that can stop the demineralization through remineralization process. This study aimed to determine the differences of enamel surface roughness after whey extract and CPP-ACP application post- extracoronal bleaching. Experimental laboratory with pre- and post-test control group design was performed on 24 first maxillary premolars which devided into 3 groups. On group I, specimens were immersed in artificial saliva. Specimens in group II were immersed in whey extract meanwhile specimens were immersed in CPP-ACP on group III. Whey extract and CPP-ACP immersions were conducted 10 minutes every 12 hours for 15 days. The enamel surface roughness test was performed twice, after extracoronal bleaching treatment and after 15 days remineralization agent application. This study result indicated significant differences between group I and group II and between group I and group III (p<0.05), but there was no significant difference between group II and group III (p>0.05). This study showed whey extract decreased more enamel surface roughness than CPP-ACP but the difference was not significant statistically. So, whey extract and CPP-ACP showed similar remineralization potential.